Employee engagement as a psychological buffer in the relationship between abusive supervision and turnover intention - Ayulanningsih; Rahmi Lubis; Risydah Fadilah (University of Merdeka Malang, 2026)
Organizations in service-intensive industries face persistent challenges related to employee turnover, particularly under high performance pressure and demanding supervisory practices. This study aims to examine the effect of abusive supervision on turnover intention and to test the moderating role of employee engagement as a psychological buffer. Using a quantitative explanatory design, data were collected through a census survey of 210 employees at a passenger vehicle distribution company in Indonesia and analyzed using variance-based structural equation modeling. The results indicate that abusive supervision has a strong positive effect on turnover intention, while employee engagement has a significant negative effect. Furthermore, employee engagement moderates the relationship between abusive supervision and turnover intention by weakening its positive impact. Additional analysis shows that the buffering effect of engagement is stronger for intention to quit and thinking of quitting than for intention to search for alternatives. These findings contribute to the literature on destructive leadership by clarifying the boundary role of employee engagement and provide practical implications for improving leadership practices and retention strategies in service-oriented organizations.